2018
DOI: 10.1177/0015732517734026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Governance Type and Economic Crises on Foreign Direct Investment Inflows in Ghana

Abstract: Global foreign direct investment (FDI) flows have increased rapidly over the last few decades. However, Ghana has not attracted much of this FDI. Investors are driven mostly by profit maximization and hence decisions to invest in an unfamiliar territory are often based on the economic and political conditions of this new territory. The current study investigates the effect of the state of governance and economic crises on FDI inflows to Ghana. Using time series data from 1960 to 2015, Vector Error Correction M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In the case of Ghana, the activities of mobile money is gaining roots. The Bank of Ghana reports that a growth rate of 129.5% in mobile money transactions from 2015 to 2016 (Bank of Ghana, 2017) as the economy experiences growth (Tuffour & Owusu, 2018;Tuffour & Mensah, 2018).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In the case of Ghana, the activities of mobile money is gaining roots. The Bank of Ghana reports that a growth rate of 129.5% in mobile money transactions from 2015 to 2016 (Bank of Ghana, 2017) as the economy experiences growth (Tuffour & Owusu, 2018;Tuffour & Mensah, 2018).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In the combined sample of all countries using especially the fixed effects results, the study found trade openness, infrastructure and market size (proxied by GDP) to have positive significant effects in attracting FDI, while institutional quality, inflation and natural resources were found to be insignificant. Tuffour and Mensah (2018) examined how economic crisis and state of governance influenced FDI inflows into Ghana using the VECM technique. Control variables included were secondary school enrolment, exchange rate, GDP, openness and technological advancement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study focused on only a single country (Ghana) and one form of foreign capital inflows (FDI). In a related study, Tuffour and Mensah (2018) Fleming (2019) analysed the effect of foreign direct investment on food security for a case study of rural Mozambique using the logit model. The research found that FDI was positively and significantly affecting food security.…”
Section: Foreign Capital Inflow and Trade Opennessmentioning
confidence: 99%